DE T E CT I ON OF A N T I B I OT I C S R E S I D UE S IN B E E F I N GHN A W A S L A U T E R HOU S E , KHA R T OU M S T A T E ,S U D AN (Journal of Veterinary Medicine and Animal Production, 2022)
The study was planned to detect antibiotics residues present in beef Ghanawa slaughterhouse, Khartoum State. The methodology was based on collection of information from the owners of the cattle (n=50) , and Veterinary Pharmacies (n=50) by means of questionnaire as well as the One Plate Test (O. P. T.) employed for estimation of antibiotics residues in different organs of the cattle. The main results showed that most of the owners did not consult veterinarians 88% (n=44). Furthermore, the majority of Veterinarians in Pharmacies 76% (n=38) left dose estimation and administration to the owners. Using one Plate Test (O. P.T.) revealed that out of 300 cattle 52(17.33%) showed positive results in one or more of their organs and there was no significant correlation level recorded for season and antibiotic residues (χ2 = 0.720, P = 0.698, P > 0.05). Out of 300 kidneys tested, 30 (10%) showed positive result, while out of 300 livers tested, 23 (7.66%) were positive, and out of 300 muscles tested 9 (3%) were positive. The age group of 4-6 years was scored high positive percentage (19.49%), (n=46 out of 236 of that age group) (χ2 = 286.260, P = 0.000, P 0.01). Moreover, the cross-breed had the higher percentage of positive (20%) (n=2 out of 10 of that breed) (χ2 = 397.293, P = 0.000, P 0.01). In conclusion, the findings of this work indicated a problem of misusing of antibiotics in cattle for meat productionand the percentage of positive samples was considered to be high.